Dental students’ perception of their educational environment in relation to their satisfaction with dentistry major: a cross-sectional study - Yoon Min Gil; Ji Soo Hong; Ju Ly Ban; Jae-Sung Kwon; Jae-Il Lee (BMC Medical Education, 2023)
Abstract Background Students’ perception of their educational environment and satisfaction with their major can reveal the extent of their readiness to practice their profession after graduation. This study aimed to evaluate dental students’ perception of their educational environment and satisfaction with their major in dentistry, as well as the relationship between these two factors. Methods An online survey was conducted in 2022 among first- to fourth-year students across 11 dental schools in Korea. The Dundee Ready Education Environment Measure (DREEM) and Academic Major Satisfaction Scale (AMSS) were used to measure the students’ perception of the educational environment and satisfaction with their major in dentistry, respectively. Results A total of 539 students participated in the survey (response rate = 18.1%). The overall mean scores of the DREEM and AMSS were 125.03 (maximum score 200) and 22.01 (maximum score 30), respectively. Fourth-year students had the lowest scores in the overall DREEM, DREEM subscales (excluding students’ perceptions of atmosphere), and AMSS. The overall DREEM scores and all DREEM subscales showed statistically significant positive and moderate correlations with AMSS (p < 0.001). Conclusion Using the DREEM, we identified areas that need improvement and the academic year (fourth year) that require proactive support. Considering the positive correlation between all DREEM subscales and the AMSS, measures to comprehensively improve the educational environment are needed to improve dental students’ satisfaction with their major.